CRITICAL SUCCESS FACTORS OF JAVA PREANGER COFFEE CHAIN IN BANDUNG REGENCY - Taufik Perdana Putra; Ratya Anindita; Suhartini Suhartini (Agricultural Socio-Economics Journal, 2018)
The Purpose of this research is to identify and analyse the critical success factor of Java Preanger Coffee  in achieving Competitive advantage. The method of these research is using qualitative methode using critical success factor analysis. Data analysis technique using descriptive analysis qualitative that compared obtained data with the theories. An Strategy to improve competitive advantage of coffee Java preanger will be the main objective of these researchThe factors that become the critical factor is aroma, serving methods, Price, Packaging, stock, roasting quality, innovation, roasting date, Serving quality, Barista role. Strategy to improve the product and make a market penetration to increase market competitiveness. Based on the result of analysis can be concluded that aroma and  roasting quality have a high point of critical sucess with score of 6.58 and 6.55 from maximum 7 points.  Packaging having the lowest score with 5.82 points. These results show us that the important role from coffee industry was the production, post harvest and processing factor that create an unique aroma and flavour for the competitive advantage and increase the benefit and value.The Purpose of this research is to identify and analyse the critical success factors of Java Preanger Coffee  in achieving Competitive advantage. The method of these research is using critical success factor analysis. The observation and data collected are used to describe factors affecting Java Preanger Coffee. The results found that the factors used for improvemen in competitive advantage of coffee Java preanger are aroma, serving methods, price, packaging, stock, roasting quality, innovation, roasting date, serving quality, and barista role. Based on the results can be concluded that aroma and  roasting quality have a high point of critical sucess with score of 6.58 and 6.55 from maximum 7 points.  Packaging has the lowest score with 5.82 points. Additionally, the important role of coffee industry was the production, post harvest and processing that create an unique aroma and flavour for the competitive advantage and increase the benefit and value.